The development of the integration of the Union State at the present stage - A. N. Zakharov (Проблемы постсоветского пространства, 2024)
The article is devoted to the study of the current state of integration of the Union State in the context of the modern transformation of the world order. The article identifies the reasons for the rapprochement between Russia and Belarus which made it possible to create and develop the integration project. Despite the objective difficulties, the two states have been successfully developing joint economic projects for a long time. Special attention is paid to the identification of external factors affecting the development of the Union State. Since the creation of the Union State western countries have pursued a policy aimed at weakening the potential of the integration association. The article examines the last years of the Union State’s activity, reveals the impact of sanctions pressure on Russia and Belarus, and analyzes the steps taken by the leaders of the two countries to further develop the integration project.